CISSP Domain 10 : operations security : video course - Harris, Shon (Pearson IT Certification, 2009)
The fast, powerful way to prepare for your CISSP exam! 30+ hours of personal video training from leading security expert Shon Harris. Achieving the (ISC)2's globally recognized CISSP can give your IT career a lift. In this DVD, the world's #1 CISSP trainer brings her legendary five-day boot camp to your computer screen. Packed with over 30 hours of instruction adapted from Shon's classes, this video course includes realistic labs, scenarios, case studies, and animations designed to build and test your knowledge in real-word settings. Preparing for the CISSP has never been this easy or convenient.